2011
DOI: 10.1109/jlt.2011.2134833
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Raman Fiber Lasers Using Hi-Bi Photonic Crystal Fiber Loop Mirrors Combined With Random Cavities

Abstract: Different multiwavelength Raman fiber lasers based on a hybrid cavity setup are proposed. The lasing schemes are based in highly birefringent photonic crystal fiber loop mirrors combined with random cavities. The Hi-Bi PCF loop mirrors are characterized by an interferometric output; whereas the random mirrors are created by cooperative Rayleigh scattering due to Raman gain. This configuration allows suppression of Rayleigh associated noise growth, while taking advantage of it as an active part of the laser cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…An intrinsic fundamental loss mechanism of an optical fiber is Rayleigh scattering (RS) [110]. When using Raman amplification besides losses due to RS there will also be losses due to double Rayleigh scattering (DRS).…”
Section: Random Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…An intrinsic fundamental loss mechanism of an optical fiber is Rayleigh scattering (RS) [110]. When using Raman amplification besides losses due to RS there will also be losses due to double Rayleigh scattering (DRS).…”
Section: Random Lasersmentioning
confidence: 99%
“…Schemes have been implemented by using four-wave mixing method through the use of reduced high nonlinear Bismuth-erbium doped fiber for Brillouin-Raman multiwavelength lasing with comb generation [117], or high-reflectivity mirror in the linear cavity for distributed feedback [118], [119]. Different multiwavelength Raman fiber lasers based in these same structural setups have been recently developed: a multiwavelength Raman fiber laser based in highly birefringent photonic crystal fiber loop mirrors combined with random mirrors [110] or based in Sagnac structures [120], [121].…”
Section: Random Lasersmentioning
confidence: 99%
“…Despite the flexibility it offers, FWM is very much dependent on the phase matching of the generated waves, thus limiting the number of wavelengths generated if the phase matching is not optimized. Under the comb filters on the other hand, many types of comb filters that have been utilized to generate multi-wavelength such as a Sagnac interferometer [4][5][6], Mach-Zehnder interferometer [7] Fabry-Perot interferometer [8], [9] and Lyot filter [10][11][12][13][14][15][16]. In this work, we demonstrate the combination of a Lyot filter and FWM in a highly nonlinear fiber (HNLF) in the laser cavity for the generation of multi-wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Pinto et al proposed different multiwavelength Raman fiber lasers. The random mirrors were created by cooperating Rayleigh scattering in the dispersion compensating fiber as a result of the high Raman gain [4]. Nasir et al demonstrated a tunable multiwavelength Brillouin-erbium fiber laser.…”
Section: Introductionmentioning
confidence: 99%